An ectopic paraganglioma supplied by the subclavian artery in the right supraclavicular fossa - Wang, Yang (J Vasc Surg Cases Innov Tech, 2019)
Paragangliomas are rare and highly vascularized neuroendocrine tumors originating from neural crest-derived paraganglionic tissue surrounding the autonomic nerve. In this case, we report a nonfunctional paraganglioma located in the right supraclavicular fossa. Both computed tomography and paraffin-embedded sections diagnosed paraganglioma. The paraganglioma was presumed to be derived from the paraganglia of the right cervical parasympathetic nerve and primarily supplied by the right subclavian artery. Because of the abundant blood supply, we performed arterial embolization before the operation. This ectopic paraganglioma is considered a rare report of a paraganglioma supplied by the subclavian artery.